(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article provides a scientific analysis of issues related to increasing the practical effectiveness of certificates issued through the national educational platform for earthquake preparedness of the population in the Republic of Uzbekistan. The study is based on the experience of Turkiye in implementing certification systems for emergency preparedness and related incentive mechanisms. In the context of Uzbekistan, an incentive model integrated with the energy, labor, education, and local governance systems is proposed to enhance the real socio-economic value of certificates. The research findings indicate that reinforcing certificates with practical benefits is an effective tool for improving the population’s level of preparedness for emergency situations.